History and develpment of urban public space in Kuala Lumpur - Harun, Nor Zalina (IIUM Press, 2015)
Kuala Lumpur began as a little town and started to take shape around 1875. Starting from this period, it grew in both physical size and population. Kuala Lumpur has emerged from a swamp and jungle area with a dominant township trading, governance and services. Between the trading and physical development, an open space development began to take shape. Open space development of Kuala Lumpur started in the late 1880’s where the British residents started to look at Kuala Lumpur as more than just a place to work but also a place to hold recreational and ceremonial activities. Accordingly, development slowly focused on providing the needed infrastructure to cater for the colonial and traders’ needs besides establishing its importance as centre of culture. A continuous network of open spaces was envisaged by the planning department and the British resident’s office that lead to the image making and the good life of the public. The early public spaces in Kuala Lumpur have evolved due to the needs of its residents at that time. The public open spaces are identified through interpretations from various literatures and have been categorised into several typologies. These typologies are according to the physical and function of the public open spaces. The earliest open spaces as identified from the review are square, streets, fields (padang), gardens, sports ground and hills.